Trajectories of psychiatric diagnoses and medication usage in youth with 22q11.2 deletion syndrome: a 9-year longitudinal study. Issue 11 (18th September 2018) - Kates, Wendy R.; Mariano, Margaret A.; Antshel, Kevin M.; Chandra, Shanel; Gamble, Hilary; Giordano, Mark; MacMaster, Eric; Mattar, Mirabelle; St. Fleur, Diane; Faraone, Stephen V.; Fremont, Wanda P.
Abstract: Background: Chromosome 22q11.2 deletion syndrome (22q11DS) is associated with high rates of psychiatric disorders, including schizophrenia in up to 30% of individuals with the syndrome. Despite this, we know relatively little about trajectories and predictors of persistence of psychiatric disorders from middle childhood to early adulthood. Accordingly, we followed youth over four timepoints, every 3 years, to assess long-term trajectories of attention-deficit hyperactivity disorder (ADHD), anxiety, mood, and psychosis-spectrum disorders (PSDs), as well as medication usage. Methods: Eighty-seven youth with 22q11DS and 65 controls between the ages of 9 and 15 years at the first timepoint (T1; mean age 11.88 ± 2.1) were followed for 9 years (mean age of 21.22 ± 2.01 years at T4). Baseline cognitive, clinical, and familial predictors of persistence were identified for each class of psychiatric disorders. Results: Baseline age and parent-rated hyperactivity scores predicted ADHD persistence [area under curve (AUC) = 0.81]. The presence of family conflict predicted persistence of anxiety disorders (ADs) whereas parent ratings of child internalizing symptoms predicted persistence of both anxiety and mood disorders (MDs) (AUC = 0.84 and 0.83, respectively). Baseline prodromal symptoms predicted persistent and emergent PSDs (AUC = 0.83). Parent-reported use of anti-depressants/anxiolytics increased significantly from T1 to T4. Conclusions: Psychiatric, behavioral, and cognitive functioning during late childhood and early adolescence successfully predicted children with 22q11DS who were at highest risk for persistent psychiatric illness in young adulthood. These findings emphasize the critical importance of early assessments and interventions in youth with 22q11DS.